MATERIAL TRACES OF PAST DEPENDENCY AND ITS CON-TEMPORARY READING IN THE URBAN SPACE OF SZCZECIN - Praczyk, Małgorzata (Porównania, 2017)
The article deals with the question of Polish-German and Polish-Soviet relations from the colonial and postcolonial perspective in the context of the urban space of Szczecin. The application of theoretical categories provided by the postcolonial studies helps to perceive the cultural landscape of the city in a different way and enables to bring out its specificity and border condition. Decisions concerning what was to be rebuilt and the way it was to be rebuilt in the city after World War II, which became Polish but situated in the area of the soviet influence, were multidimensional. The reconstruction of the city had to be defined some-where between the German heritage and the ballast of the soviet domination. In consequence this situation caused many difficulties both in the process of growing accustomed to the city and in enabling the identification with its material, architectural texture by its new, Polish inhabitants.